Kuda Menari dalam Ritual Khataman Al-Qur’an: Ekspresi Tradisi dan Inovasi Religi pada Masyarakat Desa di Kebumen - Mustolehudin Mustolehudin; Setyo Boedi Oetomo; Ulil Amrina Adilla (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2026)
The phenomenon of the Qur’an completion ceremony featuring a parade of dancing horses, which has taken place in Balingasal Village from the 1980s to the present day, serves as both a religious ritual and a marker of the community’s identity. This study aims to explore the local tradition of dancing horses in the Qur’an completion ritual in Balingasal Village, Kebumen Regency. The focus of this research is to understand the symbolic meaning, implementation process, and social function of the tradition within the context of the village community’s religious life. Data for this study were obtained through interviews, observation, and literature review. The research findings indicate that the tradition of the dancing horse in the Qur’an completion ritual is an expression of local culture and a tool for cultural communication, demonstrating a harmonious integration of Islamic values and ancestral cultural heritage within the community of Balingasal Village, which is evolving alongside modernisation. This study offers insights into patterns of cultural innovation that can be adapted and replicated in cultural regions across the archipelago where religious practices remain strong.